Drug adherence to olmesartan/amlodipine fixed combination in an Italian clinical practice setting - Degli Esposti L; Saragoni S; Buda S; Degli Esposti E (Dove Medical Press, 2014)
Luca Degli Esposti, Stefania Saragoni, Stefano Buda, Ezio Degli EspostiClicon Srl Health, Economics and Outcomes Research, Ravenna, ItalyObjective: To investigate the criteria for prescribing a combination pill for hypertensive patients, and whether the combination pill improves medication adherence.Materials and methods: This was a retrospective cohort study, performed in three Italian local health units. We selected all adult subjects who received at least one prescription of antihypertensive drugs between September 1, 2011 and December 31, 2011 (the enrollment period). The date of the first antihypertensive claim was defined as the index date. For each patient, we documented the antihypertensive drug treatments and evaluated patients’ adherence to treatment, which was calculated, separately, as the proportion of days covered in the two 6-month periods preceding and following the index date. Only patients treated with olmesartan and/or amlodipine as a single therapy, or as a two-pill combination in the period prior the index date were included. Changes in adherence levels were compared in subjects who moved to the fixed combination of olmesartan/amlodipine after the index date and in subjects who did not.Results: A cohort of 21,008 subjects with a 6-month history of a prescription of olmesartan and amlodipine as two pills in a combination treatment, or as single-pill treatment, was obtained. Subjects treated with the two-pill combination treatment moved to the olmesartan/amlodipine fixed combination treatment more frequently than did subjects with a single-pill treatment (P<0.001). Comparing the postindex date period to the preindex date period, adherence to treatment was found to be higher in the 239 subjects who moved to the olmesartan/amlodipine fixed combination therapy (from 59.0% to 78.7%; P<0.001), than in the 20,769 subjects who did not move to the olmesartan/amlodipine fixed combination therapy (from 56.3% to 63.0%, P<0.001).Conclusion: The results of the present study show that the fixed combination of olmesartan/amlodipine contributes to increasing treatment adherence in subjects previously treated with a two-pill combination therapy or a single-pill therapy.Keywords: pharmaceutical database, blood pressure, hypertension, antihypertensive therapy, multi-drug pill, proportion of days covered